Analisis Faktor-Faktor yang Memengaruhi Keputusan Hedging Perusahaan Sektor Industri Pengolahan yang Terdaftar di BEI Tahun 2014-2018 - Meridelima, Eldina; Isbanah, Yuyun (Jurnal Ilmu Manajemen, 2021)
Hedging is an alternative used to minimize risk in the company, especially risks due to exchange rate fluctuations. This study aims to determine the factors that influence corporate hedge decisions. This study uses a quantitative approach and the type of study used in secondary data. The object used in this study is a manufacturing industry sector registered in the Indonesia Stock Exchange in 2014-2018. The research sample was 41 companies through a purposive sampling technique. This study's dependent variable uses leverage, liquidity, profitability, growth opportunity, firm size, interest coverage ratio, managerial ownership, and institutional ownership. The independent variable in this study is the hedging decision. The results of this study indicate that liquidity measured by the current ratio showed a negative effect on corporate hedging decisions. The firm size measured using the natural logarithm of total assets has a positive effect on hedging decisions. Leverage, profitability, growth opportunity, interest coverage ratio, managerial ownership, and institutional ownership variables do not affect its hedging decisions. This study implies that companies with large size and low liquidity should do hedging activities to protect the company from adverse risk.